2018
DOI: 10.1111/1759-7714.12845
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profile of long non‐coding RNAs in human lung adenocarcinoma

Abstract: BackgroundLong non‐coding RNAs (lncRNAs) participate in many biological dynamics and play significant roles in gene regulation. LncRNA expression is altered in many cancers; however, the expressions and functions of lncRNA genes in lung adenocarcinoma (LAD) remain unknown.MethodsLncRNA and messenger RNA (mRNA) expression in LAD without lymphatic metastasis versus paired adjacent non‐tumor (ANT) lung tissues and LAD with versus without lymphatic metastasis were analyzed using Human LncRNA Arraystar V3.0. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The development of obesity as well as its metabolic complications is associated with dysregulation of numerous intrinsic mechanisms, which control most key metabolic processes, including cellular growth, glucose and lipid metabolism as well as insulin sensitivity and immune response (Ruderman et al 2013;Lee and Ozcan 2014;Leite et al 2014;Tam et al 2017;Wu et al 2017). It is possible that changes in classical HLA-class II molecules and non-classical HLA-class I molecules, which we observed in childhood obesity with and without insulin resistance, can contribute to these numerous intrinsic mechanisms of glucose and lipid metabolism dysregulation as well as cellular growth, because HLA-DR receptor and non-classical HLA-class I molecules play an important role in the regulation of both immune response and proliferative processes and participate in endoplasmic reticulum stress, an important factor of insulin resistance and obesity (Schaiff et al 1992;Minchenko et al 2005;Yuzefovych et al 2013;Han and Kaufman 2014;Lee and Ozcan 2014;Carosella et al 2015;Walentowicz-Sadlecka et al 2018;Yang et al 2018). Furthermore, there is data that both HLA-DR receptor and non-classical HLA-class I molecules play an important role in tumorigenesis (Kochan et al 2013;Morandi et al 2013;Leite et al 2014;Zeestraten et al 2014;Harada et al 2015;Ishigami et al 2015;Brown et al 2016;Martinez-Canales et al 2017;Winkler et al 2017;Walentowicz-Sadlecka et al 2018;Wu et al 2018).…”
Section: Discussionmentioning
confidence: 79%
“…The development of obesity as well as its metabolic complications is associated with dysregulation of numerous intrinsic mechanisms, which control most key metabolic processes, including cellular growth, glucose and lipid metabolism as well as insulin sensitivity and immune response (Ruderman et al 2013;Lee and Ozcan 2014;Leite et al 2014;Tam et al 2017;Wu et al 2017). It is possible that changes in classical HLA-class II molecules and non-classical HLA-class I molecules, which we observed in childhood obesity with and without insulin resistance, can contribute to these numerous intrinsic mechanisms of glucose and lipid metabolism dysregulation as well as cellular growth, because HLA-DR receptor and non-classical HLA-class I molecules play an important role in the regulation of both immune response and proliferative processes and participate in endoplasmic reticulum stress, an important factor of insulin resistance and obesity (Schaiff et al 1992;Minchenko et al 2005;Yuzefovych et al 2013;Han and Kaufman 2014;Lee and Ozcan 2014;Carosella et al 2015;Walentowicz-Sadlecka et al 2018;Yang et al 2018). Furthermore, there is data that both HLA-DR receptor and non-classical HLA-class I molecules play an important role in tumorigenesis (Kochan et al 2013;Morandi et al 2013;Leite et al 2014;Zeestraten et al 2014;Harada et al 2015;Ishigami et al 2015;Brown et al 2016;Martinez-Canales et al 2017;Winkler et al 2017;Walentowicz-Sadlecka et al 2018;Wu et al 2018).…”
Section: Discussionmentioning
confidence: 79%
“…Previous microarray results showed that some LncRNAs had a higher expression in LUAD tissues with lymph node metastasis. The array data have been published 16 and the gene expression omnibus accession number is GSE115734 . The microarray results showed higher expression of Linc00426 in LUAD tissues with lymphatic metastasis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only one lncRNA HLA-F-AS1 in the core ceRNA subnetwork was validated in the external datasets. Several studies had revealed the dysregulation of HLA-F-AS1 in cancers [ 48 , 49 , 50 ] while the transcript expression of HLA-F-AS1 was verified to be downregulated in lung adenocarcinoma (LAD) samples [ 49 ]. It was over-expressed in colorectal cancer (CRC) tissues and CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%